Two‐year outcomes of anti‐reflux mucosectomy in treating gastroesophageal reflux disease: A Chinese prospective cohort study - Hu, Jun Nan; Chen, Song Feng; Jia, Xing Yu; Luo, Yu; Xing, Xiang Bin; Tan, Nian Di; Zhang, Meng Yu; Zhuang, Qian Jun; Wang, Jin Hui; Xiao, Ying Lian (Journal of digestive diseases, 2023)
Objectives Anti‐reflux mucosectomy (ARMS) is an emerging and promising endoscopic treatment for gastroesophageal reflux disease (GERD). In the current study we aimed to evaluate the safety and efficacy of ARMS in treating Chinese GERD patients. Methods This was a single‐center prospective cohort study. ARMS was performed in GERD patients by an experienced endoscopist. The patients were required to undergo symptom assessment as well as endoscopic examination, high‐resolution manometry (HRM), and impedance‐pH monitoring before and after ARMS. Results Twelve patients were enrolled. Follow‐up was completed by all patients at 3 and 6 months, 11 patients at 1 year, and 8 patients at 2 years after ARMS, respectively. Symptom improvement was achieved in 66.7%, 75.0%, 72.7%, and 50.0% of the patients at 3 months, 6 months, 1 year, and 2 years after ARMS, respectively. Postoperative dysphagia was reported by 25.0%, 25.0%, 27.3%, and 25.0% of patients at 3 months, 6 months, 1 year, and 2 years after surgery, none of whom required additional invasive treatment. All patients with preoperative esophagitis healed after ARMS. For impedance‐pH monitoring parameters, number of acidic reflux episodes and the proportion of patients with acid exposure time (AET) >4.0% decreased significantly after ARMS. Conclusions ARMS was safe and effective in Chinese GERD patients. The efficacy of ARMS was not short‐term and remained evident throughout the 2‐year follow‐up. Further multicenter studies with larger sample sizes are needed to verify our findings. A total of 12 patients with gastroesophageal reflux disease (GERD) were enrolled. The proportion of patients having symptom improvement at 2 years after anti‐reflux mucosectomy (ARMS) was 50.0%. Postoperative dysphagia was reported by 25.0% of patients at 2 years after surgery. Half the patients were able to discontinue proton pump inhibitor (PPI)/potassium competitive acid blocker (P‐CAB) completely, while 75.0% of patients were able to discontinue PPI/P‐CAB by ≥50% at 2 years after surgery. The proportion of patients with acid exposure time (AET) >4.0% decreased significantly after surgery.